2020
DOI: 10.1111/1541-4337.12551
|View full text |Cite
|
Sign up to set email alerts
|

Botanical origin authentication of dietary supplements by DNA‐based approaches

Abstract: Herbal products, such as dietary supplements, have become a subject of increasing global importance for their health benefits and economic considerations. However, they have also been targets of adulteration practices, being the accurate identification of botanicals in herbal products of utmost importance to protect the health and expectations of consumers. Particularly, in the case of dietary supplements, which can have different types of formulations, the identification of plant material used in their produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 131 publications
0
47
0
Order By: Relevance
“…The global market for herbal products is rapidly expanding and expected to reach 115,000 million US$ in 2020 (Raclariu et al, 2018a) while the trade of medicinal plants will continue to advance with annual growth rates of 15-25% (Booker et al, 2012). This increasing demand for plant-based products has resulted in a proportionally increase of peer-reviewed reports of accidental contamination or intentional, economically motivated adulteration (de Boer et al, 2015;Ichim et al, 2018;Simmler et al, 2018;Grazina et al, 2020;Grosu and Ichim, 2020). A global analysis of nearly 6,000 herbal products sold in 37 countries has revealed that 27% of the products contain undeclared contaminants, substitutes, or filler species (Ichim, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The global market for herbal products is rapidly expanding and expected to reach 115,000 million US$ in 2020 (Raclariu et al, 2018a) while the trade of medicinal plants will continue to advance with annual growth rates of 15-25% (Booker et al, 2012). This increasing demand for plant-based products has resulted in a proportionally increase of peer-reviewed reports of accidental contamination or intentional, economically motivated adulteration (de Boer et al, 2015;Ichim et al, 2018;Simmler et al, 2018;Grazina et al, 2020;Grosu and Ichim, 2020). A global analysis of nearly 6,000 herbal products sold in 37 countries has revealed that 27% of the products contain undeclared contaminants, substitutes, or filler species (Ichim, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, DNA-based diagnostics of processed food products or of mixtures from different plants can sometimes be challenging (Raclariu et al, 2018b;Grazina et al, 2020), such that this principally powerful approach has to be complemented by alternative methods (Sgamma et al, 2017). Microscopy has long been used to identify herbal products in many countries, as recorded in many pharmacopoeias, because of its advantages of small amount of sample needed, speed, reliability, simplicity, and low costs (Au et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the presence of the analyte DNA is the essential prerequisite for carrying out molecular biological analyses. This is usually not the case with fats and oils [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chemical approaches can be less adequate when the formulation includes several plant species. On the contrary, DNA-based methodologies have been shown to be suitable tools for the identification/discrimination of species due to their high specificity and sensitivity, with different works reporting successful applications in the authentication of herbal products, namely food supplements or herbal infusions [15][16][17]. In this regard, different approaches including species-specific polymerase chain reaction (PCR), multiplex PCR, real-time PCR, high resolution melting (HRM) analysis, sequence characterization of amplified regions (SCAR), DNA barcoding, and next generation sequencing (NGS), among others, have been proposed to authenticate medicinal plants in herbal products [18].…”
Section: Introductionmentioning
confidence: 99%